Stochastic resource-constrained scheduling for repetitive construction projects with uncertain supply of resources and funding - Yang, I-Tung; Chang, Chi-Yi (International journal of project management, 2005)
In this paper, we schedule construction projects that are repetitively performed by similar resources (labor and equipment) from one location to another when the supply of resources and funding is not only limited but also subject to uncertainty. The supply conditions are hence expressed as probabilistic distributions in lieu of single estimates. The problem is formulated as a chance-constrained program, which is converted to a deterministic equivalent and solved by means of common linear programming techniques. The proposed chance-constrained programming model is applied to a housing project with 100 units and a real-life tunnel project to illustrate its practical usefulness in determining project acceleration strategies and in conducting risk management analyses. Model verification is performed by Monte Carlo simulations to confirm that the probability of constraint satisfaction is beyond the required confidence level.